Keto diet cookbook : 125 delicious recipes to lose weight, balance hormones, boost brain health, and reverse disease - Axe, Josh (Little, Brown Spark, 2019)
The ketogenic diet is the world's fastest growing diet, and with good reason. When practiced correctly, the keto diet has been proven to burn fat, reduce inflammation, fight cancer, balance hormones and gut bacteria, improve neurological diseases, and even increase lifespan. Unfortunately, many people remain unaware of several important factors that are crucial to the diet's success, setting them up for frustration, failure, and relapse. In KETO DIET COOKBOOK, Josh Axe builds on his national bestseller KETO DIET, offering 125 mouthwatering, keto-friendly recipes to lose weight, fight inflammation, and optimize your body's function, no matter your lifestyle or budget. Featuring a dazzling range of options for every meal of the day -- plus craving-busting snacks and decadent desserts -- KETO DIET COOKBOOK will never leave you without a delicious, satisfying option whenever hunger strikes.